1984
DOI: 10.1017/s0033291700019899
|View full text |Cite
|
Sign up to set email alerts
|

Depression following withdrawal from long-term benzodiazepine use: a report of four cases

Abstract: SynopsisDepression following withdrawal from long- or short-term use of benzodiazepines is not uncommon, yet it is under-reported in the benzodiazepine withdrawal literature. Four cases of depressive illness supervening during benzodiazepine withdrawal are reported. Depression may, it is suggested, be an integral part of the benzodiazepine withdrawal syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…A recent prospective cohort study has reported an elevated risk of incident depressive symp toms in association with new, short-term, exposure to sed ative hypnotics among medical inpatients [65], In this study, none of the subjects were exposed long term, and none exceeded standard dosages. This finding reflects ear lier observations that depression may occur as a 'paradox ical reaction' in some subjects [127,128], Depressive symptoms may also occur during withdrawal from benzo diazepines [129]. Lader [130] offered two possible inter pretations for this latter finding.…”
Section: Sedative Hypnotic Drugssupporting
confidence: 54%
“…A recent prospective cohort study has reported an elevated risk of incident depressive symp toms in association with new, short-term, exposure to sed ative hypnotics among medical inpatients [65], In this study, none of the subjects were exposed long term, and none exceeded standard dosages. This finding reflects ear lier observations that depression may occur as a 'paradox ical reaction' in some subjects [127,128], Depressive symptoms may also occur during withdrawal from benzo diazepines [129]. Lader [130] offered two possible inter pretations for this latter finding.…”
Section: Sedative Hypnotic Drugssupporting
confidence: 54%
“…Clinical experience suggests that antidepressants are the most important since depressive symptoms, sometimes amounting to major depression, are common after withdrawal (Olajide & Lader, 1984;Ashton, 1987). Several drugs have been tested for their ability to alleviate benzodiazepine withdrawal symptoms; none have been shown to be generally effective.…”
Section: Dosage Reductionmentioning
confidence: 99%
“…These medications were shown to have undesirable effects including amnesia, ataxia, tiredness, nausea, hypotension, leucopenia, hostility, confusion and depression [34], tolerance and dependence [35,36]. Benzodiazepines are still in use today for the treatment of insomnia.…”
Section: Introductionmentioning
confidence: 99%